Upaya Meningkatkan Hasil Belajar IPS Tentang Keberagaman Kegiatan Masyarakat Sekitar dan Manfaatnya Dengan Penerapan Metode Snowball Throwing pada Siswa Kelas IV SDN Wlahar 03 - Dita Kuncara Ningsih; Trikinasih Handayani; Dewi Partini (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
Learning Model The application of the Snowball Throwing Model is a learning method designed to provide benefits so that learning objectives are designed to provide students with skills in understanding what is read based on asking questions. A learning model that can generate learning outcomes for all students. The problems to be studied in this research are: (1) How is the application of the Snowball Throwing Model Learning Model in improving learning outcomes. Adipala Academic Year 2021/2022 ? (2) How much increase in learning outcomes in Theme 3 Sub-theme 1 Caring for Living Creatures after the implementation of the Snowball Throwing Model Learning Model for the fourth grade students of SD Negeri Wlahar 03 Kec. Adipala Academic Year 2021/2022 ? While the objectives of this study are: (1) To describe the application of the Snowball Throwing Model Learning Model in improving learning outcomes. Adipala Academic Year 2021/2022. (2) To find out the improvement of learning outcomes in Theme 3 Sub-theme 1 Caring for Living Creatures after the implementation of the Snowball Throwing Model Learning Model for the fourth grade students of SD Negeri Wlahar 03 Kec. Adipala Academic Year 2021/202 . The research uses the Kemmis design model based on cycles, consisting of four stages, namely action planning, implementation, observation and reflection. The subject of the research is the fourth grade of SD Negeri Wlahar 03 Kec. Adipala Academic Year 2021/2022 with 30 students in grade and the instruments used in this study were Documentation/RPP, Observation, and Tests. The results obtained from the research based on observational data improvements obtained an increase in students' understanding of learning in the pre-cycle of (62.57) cycle I (68) students got results above the Learning Completeness Standard, in the second cycle increased to (88.57). From the improvement of learning carried out by researchers, it can be concluded that the use of the Snowball Throwing Learning Model method improves learning outcomes in pre-cycle learning - the 1st cycle with an increase of 5.4%. While in the learning cycle 1 - cycle 2 increased by 20.5%.